Contractualization in higher education system: a study from the new public management's point of view - Alda Maria Duarte Araújo Castro; Raphael Lacerda de Alencar Pereira (Universidade Estadual de Maringá, 2014)
Current article discusses management forms of educational policies for higher education system focusing on the management contract used by the Program for the Support of Restructuring and Expansion Plans of Brazilian Federal Universities (REUNI). It is foregrounded on the analysis that educational policies must consider the historical contexts in which they were created and implemented, and which have lately been marked by sociopolitical and technological changes leading to reforms in the national States, with repercussions on the educational field. The bibliographical and documental study, developing a contextualized interpretation of the subject, shows that the adoption of a new management model, based on the theoretical frameworks of the new public management with business principles, has brought a new configuration to the management of the public universities where the management contract is the main operationalization instrument. The REUNI program, by adopting an organization model based on this paradigm, aimed at the efficiency and efficacy of the services, changed the organizational form of the universities, giving priority to a commercial-like relationship rather than insisting on its social function and its concern for citizenship training.